Effects of vitamin C and vitamin E on lipid peroxidation status, serum hormone, metabolite, and mineral concentrations of Japanese quails reared under heat stress (34°C) - Şahin, Kazım; Küçük, Ömer; Şahin, Nurhan; Sari, M (Imr Press, 2002)
This study was conducted to determine the effects of dietary vitamin C (L-ascorbic acid) and vitamin E (alpha-tocopherol acetate) on lipid peroxidation status measured as MDA and serum triiodothyronine (T-3), thyroxine (T-4), thyroid-stimulating hormone (TSH), adrenocorticotropic hormone (ACTH), as well as some other serum metabolite and mineral concentrations of Japanese quails reared under heat stress (34degreesC). One hundred-eighty 10-day-old Japanese quails were randomly assigned to six treatment groups, three replicates of 10 birds each. Using a 2 x 3 factorial design, the birds received two levels of vitamin C (100 and 200 mg/kg of diet) or three levels of vitamin E (125, 250, or 500 mg/kg of diet). Greater dietary vitamin E and vitamin C resulted in a greater serum T-3, T-4, and TSH (p=0.001), but lower ACTH (p=0.001) concentrations. Serum concentrations of T4 and TSH increased to a greater extent by increasing dietary vitamin C when greater vitamin E levels were fed (interaction, p=0.001). Serum glucose, urea, triglycerides, and cholesterol concentrations decreased (p=0.001), while protein and albumin concentrations increased (p=0.001) when both dietary vitamin C and vitamin E were increased. Serum activities of SGOT and SGPT were not influenced by dietary vitamin C or vitamin E (p>0.43). However, serum activity of A-P increased (p=0.001) by increasing both dietary vitamin C and vitamin E. Increasing both dietary vitamin C and vitamin E caused an increase in serum concentrations of Ca, R K (p=0.001), Fe, and Zn (p=0.01) but a decrease in serum concentrations of Na (p=0.001) and Cu (p=0.01). Interactions between vitamin C and vitamin E were detected for Ca,P, Na, and K (p=0.001). Greater dietary vitamin C and vitamin E resulted in a greater serum and liver vitamin E, C, and A (pless than or equal to0.05), but lower MDA (p=0.001) concentrations. Results of the present study conclude that supplementing a combination of dietary vitamin C (200 mg) and vitamin E (250-500 mg) offers a good management practice to reduce heat stress-related decreases in performance of Japanese quails.
Keywords: Japanese quails; heat stress; vitamin C; vitamin E; lipid peroxidation